PENGARUH BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI - Wibawa, I Gede Narya Adi; Supartha, Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Even in a company and organization that manages their human resources well, turnover will still occur which might cause losses such as the loss of experienced employees. Therefore companies and organizations try to minimize their losses by keeping the employees turnover intention low. Some factors that affect turnover intention are organizational culture and organizational commitment. This research aims to analyze the effect of organizational culture on turnover intention with organizational commitment as mediating variable at PT. Sumber Manis Trans. This research was conducted at PT Sumber Manis Trans with number of samples taken as many as 46 employees and using a saturated sample. Data collection in this study was carried out by interview and questionnaire methods. The data analysis technique used in this research is Path Analysis and Sobel Test. Based on the results of the analysis, it was found organizational culture has a negative and significant effect turnover intention, organizational culture has a positive and significant effect on organizational commitment, organizational commitment has a negative and significant effect on turnover intention, organizational commitment is a mediating variable from the influence of quality of work life. on employee performance